Safety evaluation for bridge crane based on FTA and AHP - Fei Shuai; Li Xiangdong; Fan Yali (MATEC Web of Conferences, 2018)
Starting from the development status of the lifting machinery industry, this paper analyzes the data about safety accidents of bridge cranes, and identifies the assessment indicators affecting the safety performance of bridge cranes based on fault tree analysis (FTA), including fatigue factors, human factors, environmental factors, and management factors. Then, the weights of safety evaluation indicators are determined based on analytic hierarchy process (AHP). Finally, the safety evaluation system is established and demonstrated with use case diagram and role flow chart.